Analisis Rasio Profitabilitas PT. Bank Rakyat Indonesia Tbk Periode 2020-2023 - Maulida, Wulan; Sutarsa, Monika (MASALIQ, 2025)
This study is motivated by concerns about profitability in the post-pandemic era, which affects the financial performance of a company, including Bank Rakyat Indonesia. The objective of this research is to analyze the profitability of PT Bank Rakyat Indonesia (Persero) Tbk (BBRI) during the period 2020–2023 using financial ratios Return on Assets (ROA), Return on Equity (ROE), and Gross Profit Margin (GPM). The research method used is quantitative, focusing on Bank BRI during the period 2020-2023 through time series analysis. The results indicate that in 2020, BBRI's profitability faced pressure due to the Covid-19 pandemic, leading to an increase in Non-Performing Loans (NPL), a decrease in interest income, and a rise in credit provisioning costs. However, along with the economic recovery in 2021–2023, the ROA and ROE ratios showed an increase driven by credit growth and the digitalization of banking services. This is evidenced by a significant increase in ROA from 1% in 2020 to 3% in 2022, reflecting positive growth in financial performance, although in 2023 the value stagnated. Return on Equity (ROE) has an average of 10%, which reflects the company's ability to generate profits for shareholders within a reasonable range. Gross Profit Margin (GPM) shows a fairly stable and high performance, with an average of 76%. The conclusion indicates that PT Bank Rakyat Indonesia Tbk has an excellent gross profit margin and is able to maintain efficiency in controlling direct costs relative to revenue.